A variational method for the description of the pressure-induced image mixing in GaAs-based quantum wells (2008)
ABSTARCT: The mixing between Γ and X conduction band valleys in GaAs–Ga1-xAlxAs quantum wells is investigated along the lines of a variational model. Trial wavefunctions are depending on a weighting variational parameter that accounts for the mixing by acting as a coefficient in the combination of both uncorrelated Γ and X states in the system. The dependencies of the calculated binding energy of a donor impurity and the correlated electron–hole photoluminescence peak energy upon hydrostatic pressure and quantum well width are presented.